Zakat management on asnaf muallaf : a study in Zakat Centre Universiti Teknologi MARA (UiTM) Shah Alam / Nor Haidah Yazid - Yazid, Nor Haidah (Academy of Contemporary Islamic Studies (ACIS), 2017)
This research will discuss about zakat distribution, development program and also the effectiveness of zakat to a life of student. This study was conducted at UiTM Shah Alam, where all of the informations focus on management of zakat to asnaf Muallaf in Zakat Centre in UiTM Shah Alam. Research aim to examine the management of Zakat for asnaf Muallaf in UiTM Shah Alam, including distribution and development program conducted. Objective of this research first, to examine the types of zakat assistance distribution to Asnaf Muallaf. Second, to explore the program organized by zakat UiTM. Lastly, to evaluate the effectiveness of zakat assistance towards academic and self-development performance for asnaf Muallaf. Qualitative method has use to complete all the research objective. Types of assistance distribution are allowance per month, academic fees and college fees. For program organized by Zakat Centre UiTM Shah Alam, it is Diskusi Class, mentor-mentee program and “Kita Semarak Kasih Muallaf ” program. The effectiveness of this programs was Muallaf know how and where to refers it there any problem about Islam and financial assistance give impact to muallaf further their study.